Applications of Software Engineering Ontology - Wongthongtham, Pornpit; Kasisopha, Natsuda; Komchaliaw, Surasak (IEEE, 2010)
Software engineering ontology (SE Ontology) has been developed initially to support multi-site distributed software development. It tackles the disadvantages associated with remote communication and co-ordination for software engineering projects in internationally multi-site software development environments. The SEOntology defines common shareable software engineering knowledge and typically provides software engineering concepts: what the concepts are, how they are related, and why they are related. When this generic ontology is specialized to a particular project and populated with instances which reflect the project information it provides this common understanding of project information to all the distributed members of a development team in a multi-site development environment. In this paper we present some examples of the SE Ontology applications through multi-site software development processes.